Astaxanthin supplementation enhances carcass performance, meat quality, and intestinal barrier function by modulating cecal microbiota and metabolomics in overfed Pekin ducks - Xueze Lv; Uchechukwu Edna Obianwuna; Liang Wang; Shiyong Xie; Keying An; Lulu Han; Dimei Wu; Xiaolong Qi; Shugeng Wu; Zhaofei Xia (Poultry Science)
Astaxanthin (AST), a potent antioxidant, has shown promise in improving poultry production metrics. This study investigated the effects of dietary AST on carcass traits, breast muscle composition, intestinal barrier function, cecal microbiota, and metabolomics in overfed Pekin ducks. A total of 150 one-day-old male Pekin ducks were assigned to five groups: Control (CON, basal diet), low-dose AST (LDG, 40 mg/kg), medium-dose (MDG, 80 mg/kg), high-dose (HDG, 120 mg/kg), and an ad libitum-fed group (ALG), and the feeding trial lasted for 42 days. Our findings revealed that AST significantly enhanced live and carcass weights, increased breast muscle mass in the HD group, and promoted subcutaneous fat deposition MD group, (P < 0.05). Supplementation of AST improved breast muscle amino acid profiles, especially phenylalanine, alanine, arginine, lysine, and tryptophan, and shifted fatty acid composition by reducing saturated fatty acids and increasing mono- and polyunsaturated fatty acids, notably in the MDG (P < 0.05). Astaxanthin reduced serum total and low-density lipoprotein cholesterol while increasing high-density lipoprotein cholesterol (P < 0.05). Furthermore, astaxanthin enhanced gut barrier integrity by lowering serum nitric oxide, endotoxin, and D-lactate levels and upregulating jejunal Mucin-2 and occludin gene expression (P < 0.05). Microbiota analysis revealed increases in Bacteroidota, Firmicutes, and Actinobacteria, with beneficial associations between gut integrity and Weissella and Lactobacillus, and negative correlations with Faecalibacterium. Metabolomics identified enrichment of glycerophospholipid, tryptophan, glutathione, glycine‑serine-threonine, and aminoacyl-tRNA biosynthesis pathways. Key upregulated metabolites included 5-methoxyindoleacetate and glyceric acid, while Lysophosphatidylcholines (LysoPCs) were downregulated. 6-hydroxymelatonin and creatine were enriched but not significant. Microbiota-metabolome correlations indicated negative associations between Weissella and LysoPCs, Faecalibacterium and creatine, and a positive link between Collinsella and glyceric acid (P < 0.05), favoring gut health. Overall, AST improved carcass traits and intestinal function in overfed ducks via microbiota and metabolic modulation.